The role of the spleen in experimental autoimmune thyroiditis. - Weetman, A P (1984)
We have investigated the role of the spleen in the humoral and cellular immune response of rats with experimental autoimmune thyroiditis (EAT) induced by immunization with thyroglobulin and Freund's complete adjuvant. Animals subjected to splenectomy within 4 days of immunization developed lower thyroglobulin antibody levels and less severe thyroiditis compared to sham operated controls. There was no impairment in the ability of the animals to recover spontaneously from the disease after splenectomy. Together with the results obtained using splenocyte infusions, this suggests that suppressor cell production within the spleen plays only a small part in the normal immunological control which is presumably responsible for spontaneous regression of the disease.